Economical preparation of Fe3O4/C/CG and Fe/C/CG composites as microwave absorbents by recycling of coal gangue. (February 2022) - Wang, Yake; Liang, Liping; Zhu, Baoshun; Tian, Yuming; Li, Guomin
Highlights: The gangue is recycled to prepare ceramic-based microwave absorbents. The Fe3 O4 /C/CG and Fe/C/CG composites possess excellent performance. Impedance matching and interfacial polarization play a key role to MA property. The novel method realizes the recycling of gangue and cuts the cost of absorbents. Abstract: Pollution is a pressing problem in the context of sustainable development, a solution to which is to reutilize waste resources. Herein, coal gangue was recycled to prepare Fe3 O4 /C/CG and Fe/C/CG composites for microwave absorption via a facile method. The synthesis process involves loading a precursor solution of starch and ferric nitrate onto coal gangue matrix and then conducting the in-situ carbothermal reduction. The initial starch mass and carbothermal temperature significantly affect the dielectric and magnetic properties, further affect microwave absorption performance of the composites. For the Fe3 O4 /C/CG and Fe/C/CG composite, the minimum reflection loss could reach −45.1 dB and −27.8 dB, respectively. And the maximum effective absorption bandwidth of Fe/C/CG was 4.7 GHz. The strong microwave attenuation and impedance matching, which stemmed from the conductive graphitized carbon, the abundant interfaces of the highly dispersed carbon and iron species on the matrix, must account for the excellent performance. Graphical abstract: Coal gangue, solid waste, was recycled to prepare Fe3 O4 /C/CG and Fe/C/CG composites for microwave absorption via a facile method. These graphs showed the microwave absorption performance of Coal Gangue, Fe3 O4 /C/CG and Fe/C/CG composites. Image, graphical abstract